난시교정각막절개술과 라식 수술 병합수술의 임상결과 - 김부기(Bu Ki Kim), 문수정(Su Joung Mun), 이대규(Dae Gyu Lee), 정영택(Young Taek Chung) (Daihan angwa haghoi jabji, 2016)
목적: 고도난시 환자를 대상으로 난시교정각막절개술을 통해 난시를 줄인 뒤 라식 수술을 시행하여 임상성적을 평가하고자 하였다. 대상과 방법: 2012년도 10월부터 2014년도 9월까지 19명, 35안을 대상으로 난시교정각막절개술 후 라식 수술을 받은 환자를 대상으로 연구를 시행하였다. Amaris Ablation depth table을 이용하여 난시교정각막절개술 전후 예상 각막절삭량을 비교하였고, 술 전과 술 후 1주, 1개월, 3개월, 6개월에 나안시력, 굴절력, 효율성, 안전성, 예측성 등을 비교하였다. 결과: 난시도수의 양은 난시교정각막절개술 후 61.43 ± 14.62% 감소하였고, 라식 수술 후 91.65 ± 8.68% 감소하였다. 예상 각막절삭량은 난시교정각막절개술 후 18.72 ± 11.77%의 감소가 있었고, 병합수술 6개월째 85.71%에서 구면렌즈대응치가 ±0.5D로 유지되었으며 수술 중, 수술 후 합병증은 관찰되지 않았다. 결론: 고도난시 환자에서 난시교정각막절개술과 라식 수술 병합수술은 각막절삭량을 감소시키는 데 효과적이고 시력, 굴절력 등 임상결과에서 좋은 결과를 보였다. Purpose: To evaluate the clinical outcomes of a combined procedure of astigmatic keratotomy (AK) and laser in situ keratomileusis (LASIK) for the correction of high astigmatism. Methods: Thirty-five eyes of 19 patients who had astigmatic keratotomy were studied. The patients had a secondary procedure, LASIK, to correct the residual refractive error. Follow-up visits were at 1 week, 1 month, 3 months, and 6 months. The outcome measures included uncorrected distance visual acuity, refractive error, efficacy, safety, and predictability. We compared preoperative and post-AK expected corneal ablation depth using an Amaris Ablation depth table. Results: After astigmatic keratotomy, astigmatism was reduced by 61.43 ± 14.62%, and after LASIK, astigmatism was reduced by 91.65 ± 8.68%. Expected corneal ablation depth was reduced by 18.72 ± 11.77% after astigmatic keratotomy. The proportion of eyes with spherical equivalent 0.5 D or less was 85.71% at 6 months after the combined procedure of astigmatic keratotomy and LASIK. No intraoperative or postoperative complications were observed. Conclusions: This study showed the combined procedure of astigmatic keratotomy and LASIK is effective for visual acuity, refraction, and reduction in corneal ablation depth. KCI Citation Count: 1